PTEN loss promotes Warburg effect and prostate cancer cell growth by inducing FBP1 degradation - Song, Changze; Zhang, Jianong; Liu, Xiao; Li, Meilu; Wang, Dejie; Kang, Zhijian; Yu, Jiaao; Chen, Jiuwei; Pan, Hongxin; Wang, Honglei; Li, Guangbin; Huang, Haojie (Frontiers in Oncology, 2022)
Rationale: Fructose-1,6-bisphosphatase (FBP1) is a tumor suppressor and a key enzyme negatively regulating Warburg effect in cancer. However, regulation of FBP1 protein expression and its exact role in prostate cancer (PCa) is largely unclear. Phosphatase and tensin homolog (PTEN) is one of the most frequently deleted tumor suppressor genes in human PCa. However, the role of PTEN loss in aberrant Warburg effect in cancer remains poorly understood. Methods: Expression of PTEN and FBP1 was analyzed in several PCa cell lines and prostate tumor tissues in mice. Western blot (WB) and RT-PCR approaches were used to examine how PTEN regulates FBP1 expression. Co-immunoprecipitation (co-IP) and in vivo ubiquitination assays were used to define the regulatory mechanisms. A PCa xenograft model was employed to determine the impact of PTEN regulation of FBP1 on PCa growth in vivo. Result: We demonstrated that in a manner dependent of PI3K/AKT signal pathway PTEN regulated FBP1 expression in various PCa cell lines and tumors in mice. We confirmed that this regulation took place at the protein level and was mediated by SKP2 E3 ubiquitin ligase. Mechanistically, we showed that serine 271 phosphorylation of FBP1 by cyclin-dependent kinases (CDKs) was essential for SKP2-mediated degradation of FBP1 protein induced by PTEN loss. Most importantly, we further showed that loss of PTEN expression enhanced Warburg effect and PCa growth in mice in a manner dependent, at least partially on FBP1 protein degradation. Conclusions: Our results reveal a novel tumor-suppressive feature of PTEN in restraining FBP1 degradation and the Warburg effect. These results also suggest that prohibiting FBP1 protein degradation could be a viable therapeutic strategy for PTEN-deficient PCa.